2007
DOI: 10.1002/jmr.852
|View full text |Cite
|
Sign up to set email alerts
|

SFM studies of carbon ion induced damages in plasmid DNA

Abstract: In this study we present for the first time detailed scanning force microscopy (SFM) investigations of carbon ion induced damages in plasmid DNA in order to obtain information about the biological effectiveness of particle radiation. For this purpose, we have combined SFM and gel electrophoresis measurements in a dose range between D = 0 Gy and 5000 Gy. After irradiation with C ions, the percentage of double-strand breaks (DSBs) increases drastically, i.e. from initially 0% for D = 0 Gy to 38% for D = 5000 Gy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Other investigators have subsequently applied AFM for further studies of radiation induced DNA damage (Murakami et al, 2000 ; Brons et al, 2004 ; Psonka et al, 2005 ; Brezeanu et al, 2007 ; Elsässer et al, 2008 ; Ke et al, 2008 ; Gudowska-Nowak et al, 2009 ; Lee et al, 2009 ; González et al, 2012 ). Of particular relevance to measurement of short DNA fragments by high-LET radiations, Psonka-Antonczyk et al ( 2009 ) investigated DNA breakage by Ni ions and observed a reduced average DNA fragment length after 340-Gy irradiation when compared to X-ray irradiations.…”
Section: Afm Investigation Of Radiation-induced Plasmid Dna Fragmentamentioning
confidence: 99%
“…Other investigators have subsequently applied AFM for further studies of radiation induced DNA damage (Murakami et al, 2000 ; Brons et al, 2004 ; Psonka et al, 2005 ; Brezeanu et al, 2007 ; Elsässer et al, 2008 ; Ke et al, 2008 ; Gudowska-Nowak et al, 2009 ; Lee et al, 2009 ; González et al, 2012 ). Of particular relevance to measurement of short DNA fragments by high-LET radiations, Psonka-Antonczyk et al ( 2009 ) investigated DNA breakage by Ni ions and observed a reduced average DNA fragment length after 340-Gy irradiation when compared to X-ray irradiations.…”
Section: Afm Investigation Of Radiation-induced Plasmid Dna Fragmentamentioning
confidence: 99%
“…This issue and the subsequent ones were edited by us (except those written by our own laboratory that were handled by Heinrich Hörber, a new editor of JMR following the addition of the keyword AFM to the journal's topic list). The first special issue contained three reviews and 14 research articles …”
Section: Afmbiomed Conferencesmentioning
confidence: 99%
“…The first special issue contained three reviews 5-7 and 14 research articles. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] The…”
Section: Afmbiomed Conferencesmentioning
confidence: 99%
“…target for biological effects of ionising radiation, investigation of DNA damage has attracted much attention in recent years [1][2][3][4][5][6][7][8][9]. After irradiation, much serious damage, such as singlestrand breaks, double-strand breaks or base damage can occur in a DNA molecule.…”
mentioning
confidence: 99%
“…Nucleic acids and especially DNA have been extensively investigated with SFM [5][6][7][8][9][19][20][21][22][23], since its invention by Binning and collaborators in 1986 [24]. So far, SFM studies of DNA focused in particular on visualising the DNA structure [19,25,26], manipulating DNA on surfaces [27,28] or using it as a conductive material for future molecular electronics [29][30][31].…”
mentioning
confidence: 99%